Characteristics and in vitro properties of potential probiotic strain Fructobacillus tropaeoli KKP 3032 isolated from orange juice - Mikołajczuk-Szczyrba, Anna; Wojtczak, Adrian; Kieliszek, Marek; Sokołowska, Barbara (Folia microbiologica, 2025)
Fructobacillus, a Gram-positive, non-spore-forming, facultative anaerobic bacterium, belongs to the fructophilic lactic acid bacteria (FLAB) group. The group's name originates from fructose, the favored carbon source for its members. Fructobacillus spp. are noteworthy for their distinctive traits, captivating the interest of scientists. However, there have been relatively few publications regarding the isolation and potential utilization of these microorganisms in the industry. In recent years, F. tropaeoli has garnered interest for its promising role in the food and pharmaceutical sectors, although the availability of isolates is rather limited. A more comprehensive understanding of Fructobacillus is imperative to evaluate their functionality in the industry, given their unique and exceptional properties. Our in vitro study on Fructobacillus tropaeoli KKP 3032 confirmed its fructophilic nature and high osmotolerance. This strain thrives in a 30% sugar concentration, shows resistance to low pH and bile salts, and exhibits robust autoaggregation. Additionally, it displays significant antimicrobial activity against foodborne pathogens. Evaluating its probiotic potential, it aligns with EFSA recommendations in antibiotic resistance, except for kanamycin, to which it is resistant. Further research is necessary, but preliminary analyses confirm the high probiotic potential of F. tropaeoli KKP 3032 and its ability to thrive in the presence of high concentrations of fructose. The results indicate that the isolate F. tropaeoli KKP 3032 could potentially be used in the future as a fructophilic probiotic, protective culture, and/or active ingredient in fructose-rich food.
Keywords: FLAB; Hydrophobicity; ovocné a zeleninové šťávy; Fructose; Bile salts; probiotika; antibakteriální látky; Citrus sinensis; Autoaggregation; Hydrogen-Ion Concentration; fruktosa; potravinářská mikrobiologie; Antimicrobial activity; pomerančovník čínský; koncentrace vodíkových iontů; Fruit and Vegetable Juices; Anti-Bacterial Agents; Food Microbiology; Leuconostocaceae; Probiotics; Fructophilic probiotic